2017
DOI: 10.1097/md.0000000000008928
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial stromal sarcoma in combination with mixed type endometrial carcinomas

Abstract: Rationale:Endometrial stromal sarcoma (ESS) is rare, representing only approximately 0.2% of all uterine malignancies. Mixed type endometrial carcinomas (MT-ECs) are rare tumors with both type I and II features, and are difficult to diagnose. Cases of ESS and MT-ECs coexisting in the same patient are extremely rare. This study aimed to describe a case of ESS in combination with MT-ECs in a 47-year-old premenopausal woman.Patient concerns:A woman presented to the hospital complaining of occasional abdominal pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This is of particular interest, since RUNX3 is a paradoxical oncogene in HNSC (while generally being a tumor suppressor) and is connected to the transforming growth factor b (TGF-b) pathway and fibrosis [33,34], thus suggesting that the activation of this regulatory interaction plays a significant role in the microenvironmental characteristics of this neoplasia. In keeping with these findings, we evidence that SEMA4D is also found by our analysis in Uterine Corpus Endometrial Carcinoma (UCEC), in this case regulated by Paired box gene 8 (PAX8 , Table S1) which is a driver of uterine neoplasms and, again, associates with fibrosis [35,36].…”
Section: Resultssupporting
confidence: 89%
“…This is of particular interest, since RUNX3 is a paradoxical oncogene in HNSC (while generally being a tumor suppressor) and is connected to the transforming growth factor b (TGF-b) pathway and fibrosis [33,34], thus suggesting that the activation of this regulatory interaction plays a significant role in the microenvironmental characteristics of this neoplasia. In keeping with these findings, we evidence that SEMA4D is also found by our analysis in Uterine Corpus Endometrial Carcinoma (UCEC), in this case regulated by Paired box gene 8 (PAX8 , Table S1) which is a driver of uterine neoplasms and, again, associates with fibrosis [35,36].…”
Section: Resultssupporting
confidence: 89%
“…We experienced a case combining EC and ESS, which has not been described in many reports as summarized in Table 1. [6][7][8][9] EC arises most commonly in the perimenopausal or postmenopausal age group, in the fifth and sixth decades of life, with a mean age of 56 years. 10 It has been suggested that a high proportion of ovarian ECs arise from endometriotic cysts, since ipsilateral ovarian and pelvic endometriosis is seen in up to 42% of ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, uterine leiomyosarcoma is the most universal malignant mesenchymal tumor, accounting for 1% of uterine malignant tumor (1). ESS accounts for 0.2% of malignant uterine tumors (2). The coexistence of these two kinds of malignant tumours in one patient is extremely rare, especially when the volume of ESS accounts for less than 1% of the tumour mass but causes ovarian and pelvic metastases.…”
Section: Case Presentationmentioning
confidence: 99%